Effects of the COVID-19 pandemic on vocational education and training: international perspectives of policy makers and practitioners - (:unkn) unknown (Barbara Budrich, 2022)
"In a series of virtual bilateral workshops held from February to April 2021, the German Federal Ministry of Education and Research (BMBF) and their partner ministries in seven countries - Costa Rica, Ghana, Israel, Italy, Russia, South Africa, and USA - discussed the effects of the COVID-19 pandemic on Vocational Education and Training (VET), employment, and youth. GOVET (German Office for International Cooperation in VET) asked policy makers, researchers, and practitioners to share their experiences, fi rst lessons learned, best practices, and response strategies. This publication documents the outcomes. The contributions range from hands-on practical reports to in-depth VET research findings, from rather analytical perspectives to policy consultancy and strategic ideas." (Publisher, BIBB-Doku)
Keywords: S 1.3 Berufliche Erstausbildung; I 2.2.1 Westeuropa; I 2.2.2 Osteuropa; I 2.3.1 Afrika; I 2.3.2 Nordamerika; I 2.3.3 Lateinamerika; I 2.3.4 Asien; 370; Berufsbildung; Berufsausbildung; Pandemie; Auswirkung; Ausbildungsstellenmarkt; Jugendlicher; Berufseinmündung; Ausbilder; Medienkompetenz; Digitalisierung; Digitalkompetenz; E-Learning; Psychische Faktoren; Bundesrepublik Deutschland; Costa Rica; Ghana; Israel; Italien; Russland; Südafrika; USA